Modal Analysis of Free-Inverted Wilson Tennis Racket with 1st Type and 2nd Type of Damper - Rozi Saferi; Asmara Yanto; Ismet Eka Putra (Jurnal Teknik Mesin (JTM), 2016)
One way that can be used to analyze vibration in structures is the modal method of analysis. With this method vibration can be measured when the structure is working, so get the form of vibration mode and vibration values with different frequency levels. If the frequency of the structure in operation is known, then the structure can be controlled so that it does not work on its private frequency, so that the vibrations that occur in the structure are at a safe level. The objective of this research is to know the mechanism of reconstruction of disturbance force on tennis racket structure that vibrates and determines the personal frequency through the test. Then determine the time-frames style graph. In testing, the Wilson brand test racket was given a type 1 and type 2 damper with a weight of 320 grams and a 697mm long vertical hanging with a free-to-pedestal condition. After the software was run, an excitation style with impact hammer was applied to the top of the racket. Measurement of response is done by recording FRF (frequency domain) and coherence graph. The sampling results are stored in * .txt extensioned files and processed with microsoft excel to get real FRF and imaginary FRF graphics. The test is done several times by varying the accelerometer position of 8 points and 2 types of silencer. From the capital test the analysis of the specimen is hung freely with the silencer, then obtained the personal frequency of the test racket with a lower silencer than the personal frequency of the system without damper with a difference of 2 Hz. The three lowest vibration modes of the free-hanging system of the experimental results are the first mode of a half-wave graph forming a peak, the second mode being a one-wave graph forming a single valley peak, and the third mode being a one-and-a-half wave graph of the two valleys. The damping of the test structure is different at each test point and at any given frequency range.